2018
DOI: 10.30773/pi.2017.05.24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Levels of Nesfatin-1 and Ghrelin Hormones in Patients with Moderate and Severe Major Depressive Disorders

Abstract: Objective The goal of this study was to evaluate the importance of nesfatin-1, acylated and des-acylated ghrelin, which are known as energy regulatory hormones, in patients with moderate and severe major depression disorders (MDD). Methods Thirty patients with a moderate degree of MDD and, 30 with a severe degree of MDD were used as participants in this study. Thirty subjects without depression were enrolled as a control group. The Hamilton Depression Rating Scale was used to classify the patients with MDD. Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Algul et al (30) have reported that the acylated ghrelin levels were found to be significantly higher in severe major depression disorders as compared to control group. In our data, SRQ-D score in FD patients with high levels of acylated ghrelin was significantly higher compared to that in low levels of acylated ghrelin.…”
Section: Discussionmentioning
confidence: 97%
“…Algul et al (30) have reported that the acylated ghrelin levels were found to be significantly higher in severe major depression disorders as compared to control group. In our data, SRQ-D score in FD patients with high levels of acylated ghrelin was significantly higher compared to that in low levels of acylated ghrelin.…”
Section: Discussionmentioning
confidence: 97%
“…Besides the correlation with self-reported anxiety, circulating NUCB2/nesfatin-1 was also associated with reported depression in a mixed-sex population [ 122 ], with NUCB2/nesfatin-1 levels rising with increasing severity of depression [ 123 , 124 ], and correlated with inflammatory markers such as IL-6 and C-reactive protein as well as corticosterone under these conditions [ 125 ]. Higher NUCB2/nesfatin-1 levels were subsequently shown in patients reporting depression associated with subclinical hypothyroidism [ 126 ], leading to the hypothesis of nesfatin-1 being involved in these symptoms.…”
Section: Implications Of Nesfatin-1 In the Development Of Anxiety mentioning
confidence: 99%
“…This finding indicates that in the depressed population elevated ghrelin may have roles outside of increasing eating behavior and may interact to influence the HPA axis resulting in elevated stress response. Furthermore, work by Algul et al found both acylated and deacylated serum ghrelin level were elevated in MDD patients and increases in ghrelin concentration significantly correlated with disease severity ( 84 ).…”
Section: Ghrelin As a Potential Biomarker Of Gut-brain Interactions Imentioning
confidence: 99%